Pengaruh Latar Belakang Pendidikan dan Motivasi Guru PAUD Terhadap Stres Mengajar: (Penelitian Ekspost Facto di Kota Probolinggo) - Achmad Sya'dullah (At- Ta'lim : Jurnal Pendidikan, 2016)
Stress can lead teachers to teach teachers act uncontrol such as physical violence or verbal. This can cause stress teach inability in dealing with problems in learning, while the incapacity is due to the educational background of the teachers and the teaching of each teacher motivation. This study aims to determine the effect of educational background and motivation of teachers to teach to stress teaching in early childhood education (ECD), which is located in the city of Probolinggo. Contributions background of teacher education and teaching motivation was instrumental to the high stress of teaching the teachers, because by knowing the cause of the stress of teaching will be useful to reduce violence against students. This research is quantitative comparative, ex post facto with survey data retrieval at any early childhood teachers in Probolinggo in 2014. Data were analyzed using Anova 2 T test track and research design Treatment By Level 2 x 2. The results showed that teachers with early childhood education background and highly motivated graduates (= 37 and s = 5.12) lower stress than teachers with educational background in early childhood education graduates and non low motivation (= 51 and s = 6.8). so that the necessary background behind belakng ECD graduates to become early childhood teachers, but it is also necessary motivation to teach.